Aqueous Levels of Pigment Epithelium-Derived Factor and Macular Choroidal Thickness in High Myopia - Wei Chen; Yubo Guan; Guanghui He; Zhiwei Li; Hui Song; Shiyong Xie; Quanhong Han (Journal of Ophthalmology)
Purpose. To investigate the correlation between aqueous and serum levels of pigment epithelium-derived factor (PEDF) and macular choroidal thickness in high myopia patients, both with and without choroidal neovascularization (CNV). Methods. Serum and aqueous levels of PEDF were measured by enzyme-linked immunosorbent assay in 36 high myopia patients (36 eyes) with no CNV (non-CNV group), 14 high myopia patients (14 eyes) with CNV (CNV group), and 42 nonmyopia patients (42 eyes) (control group). Macular choroidal thickness was measured by enhanced-depth imaging optical coherence tomography. Results. Aqueous levels of PEDF were significantly higher in CNV group compared with non-CNV (P<0.001) and control (P<0.001) groups. Macular choroidal thicknesses were significantly decreased in the non-CNV and CNV groups compared with the control (P<0.001) group. A statistically significant difference (P=0.012) was found between the CNV and non-CNV groups. There was a positive correlation between aqueous PEDF and macular choroidal thickness in the non-CNV group (P=0.005), but no correlation with the CNV group. No correlation between serum PEDF and macular choroidal thickness was detected in the three groups. Conclusion. Variations in aqueous PEDF levels coincide with changes in macular choroidal thickness in high myopia patients with no CNV, while no such relationship exists in high myopia patients with CNV.